Understanding the pathophysiology of the human TB lung granuloma using in vitro granuloma models. (August 2016) - Bhavanam, Sudha; Rayat, Gina R; Keelan, Monika; Kunimoto, Dennis; Drews, Steven J
Tuberculosis remains a major human health threat that infects one in three individuals worldwide. Infection with Mycobacterium tuberculosis is a standoff between host and bacteria in the formation of a granuloma. This review will introduce a variety of bacterial and host factors that impact individual granuloma fates. The authors describe advances in the development of in vitro granuloma models, current evidence surrounding infection and granuloma development, and the applicability of existing in vitro models in the study of human disease. In vitro models of infection help improve our understanding of pathophysiology and allow for the discovery of other potential models of study.